Unveiling the Botanical Riches: Enhancing Quality Control and Stability Assessment of Sa-Tri-Lhung-Klod Remedy Extract Through HPLC Profiling and Anti-inflammatory Potency Evaluation - Inprasit, Janjira; Ruangnoo, Srisopa; Itharat, Arunporn; Makchuchit, Sunita; Pipatrattanaseree, Weerachai; Davies, Neal M (Asian Medical Journal and Alternative Medicine, 2024)
Introduction: Sa-Tri-Lhung-Klod (ST) remedy is a Thai traditional medicine preparation, used for post-partum care including excreting amniotic fluid, reducing inflammation, and improving blood circulation. The standard quality values and the stability of ST have not been reported. Quality control and stability testing are necessary to determine and insure the standard quality of ST remedy. Objectives: To evaluate the quality control of herbal components according to Thai Herbal Pharmacopoeia (THP). The stability of ST extracts was examined using high performance liquid chromatography (HPLC) and anti-inflammatory activity was measured. Methods: The quality assessment of the ST and plant components was performed by moisture content, total ash, acid-insoluble ash, extractive value, and tannin content, following the THP method. The stability testing of ST extracts stored under accelerated conditions for six months was performed, and the percentage of the remaining compounds were evaluated using HPLC and tested for anti-inflammatory activity on nitric oxide (NO) inhibitory assay in RAW264.7 cells. Results: Quality control of ST and plant components met THP requirements, and the tannin content of ST increased upon extraction. ST ethanolic extract (STE) and the remaining compounds exhibited stability after 6 months and anti-inflammatory activity on nitric oxide inhibition assay was retained from day 0 to day 180. However, ST aqueous extract (STW) was unstable from day 30. Conclusions: The first report of quality control and stability testing of ST is outlined. ST and plant components comply with THP standard requirements. STE can be stored at room temperature for up to two years, whereas STW requires refrigeration in order to extend its shelf life.